Identification of a novel LAMA2 c.2217G > A, p.(Trp739*) mutation in a Moroccan patient with congenital muscular dystrophy: a case report - Youssef El Kadiri; Ilham Ratbi; Fatima Zahra Laarabi; Yamna Kriouile; Abdelaziz Sefiani; Jaber Lyahyai (BMC, 2021)
Abstract Background Merosin-deficient congenital muscular dystrophy type 1A (MDC1A) is a rare autosomal recessive genetic condition caused by deleterious mutations in the LAMA2 gene encoding the laminin-α2 chain. It is the most frequent subtype of congenital muscular dystrophies (CMDs) characterized by total laminin-α2 deficiency with muscle weakness at birth or in the first six months of life. To the best of our knowledge, this study reports the first molecular diagnosis and genetic defect of this heterogeneous form of CMD performed in a Moroccan medical genetic center using next-generation sequencing (NGS). It allows us to expand the mutational spectrum of the LAMA2 gene. Case presentation We report the case of a female Moroccan child with clinical and paraclinical features in favor of a CMD. She has global congenital hypotonia with generalized muscle weakness, psychomotor retardation, increased serum creatine kinase, and normal brain scan at the age of six months. Targeted NGS leads to the identification of a novel homozygous nonsense mutation c.2217G > A, p.(Trp739*) in the exon 16 of LAMA2. Sanger sequencing confirmed this mutation in the affected patient and showed that her parents are heterozygous carriers. Conclusions A modern genetic analysis by NGS improves the genetic diagnosis pathway for adequate genetic counseling of affected families more precisely. An accession number from the National Center for Biotechnology Information (NCBI) ClinVar database was retrieved for this novel LAMA2 mutation.